Novelty selectively permits learning-associated plasticity in ventral tegmental-hippocampal-prefrontal circuitry - Park, Alan Jung (Frontiers in Behavioral Neuroscience, 2023)
Modifying established behavior in novel situations is essential, and patients with neuropsychiatric disorders often lack this flexibility. Understanding how novelty affects behavioral flexibility therefore has therapeutic potential. Here, novelty differentially impacts connectivity within the ventral tegmental-hippocampal-medial prefrontal (VTA-HPC-mPFC) circuit, thereby enhancing the ability of mice to overcome established behavioral bias and adapt to new rules. Circuit connectivity was measured by local field potential (LFP) coherence. As mice exposed to novelty learned to overcome previously established spatial bias, the ventral HPC (vHPC) strengthens its coherence with the VTA and mPFC in theta frequency (4-8Hz). Novelty or learning did not affect circuits involving the dorsal HPC (dHPC). Without novelty, however, mice continued following established spatial bias and connectivity strength remained stable in the VTA-HPC-mPFC circuit. Pharmacologically blocking dopamine D1-receptors (D1Rs) in the vHPC abolished the behavioral and physiological effects of novelty. Thus, novelty promotes behavioral adaptation by permitting learning-associated plasticity in the vHPC-mPFC and VTA-vHPC circuit, a process mediated by D1Rs in the vHPC.